THE GENDER AND AGE STRUCTURE OF THE POPULATION OF COVASNA COUNTY, AT THE 2011 CENSUS - George-Bogdan TOFAN; Adrian NIŢĂ; Bogdan-Nicolae PĂCURAR (Analele Universităţii din Oradea: Seria Geografie, 2016)
This study presents a synthesis regarding the territorial distribution of the gender and age structure of the population in Covasna County, in 2011. We began by reviewing the characteristics regarding gender structure, and both genders (BG), followed by the male population (M) and the female population (F), as well as the age groups, beginning with young people (0-19 years), adults (20-59 years) and ending with the elderly, over 60 years. Moreover, for a clearer view of the male to female population ratio, we employed the most suggestive indicator, the feminity index.